Political Jurisdictions in Heterogeneous Communities - Alesina, Alberto; Baqir, Reza; Hoxby, Caroline (Journal of Political Economy, 2004)
We investigate whether political jurisdictions form in response to the trade‐off between economies of scale and the costs of a heterogeneous population. We consider heterogeneity in income, race, ethnicity, and religion, and we test the model using American school districts, school attendance areas, municipalities, and special districts. We find strong evidence of a trade‐off between economies of scale and racial heterogeneity; we also find evidence of a trade‐off between economies of scale and income heterogeneity. Conversely, we find little evidence that ethnic or religious heterogeneity shapes jurisdictions. To clarify the direction of causality between heterogeneity and jurisdictions, we exploit shocks to racial heterogeneity generated by the two world wars.